2009
DOI: 10.1093/jxb/erp240
|View full text |Cite
|
Sign up to set email alerts
|

Insect peptide metchnikowin confers on barley a selective capacity for resistance to fungal ascomycetes pathogens

Abstract: The potential of metchnikowin, a 26-amino acid residue proline-rich antimicrobial peptide synthesized in the fat body of Drosophila melanogaster was explored to engineer disease resistance in barley against devastating fungal plant pathogens. The synthetic peptide caused strong in vitro growth inhibition (IC50 value ∼1 μM) of the pathogenic fungus Fusarium graminearum. Transgenic barley expressing the metchnikowin gene in its 52-amino acid pre-pro-peptide form under the control of the inducible mannopine synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
66
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 67 publications
(68 citation statements)
references
References 43 publications
2
66
0
Order By: Relevance
“…2 Assessment of metchnikowin effects on powdery mildew fungus during its interaction with transgenic barley provided evidence that the antifungal peptide improves the resistance of plant as if it impedes the development of functional haustorium due to increased rate of hypersensitive response (HR) and development of cell wall apposition (CWA). 2 Comprehensive study on possible latent influence of metchnikowin on the defense system of plant revealed that the SAR and ISR pathways as well as redox status of metchnikowin-expressing barley plants are potentiated during interaction with powdery mildew fungus. 99 In Phenylpropanoid pathway, the PAL-1 gene expression profile demonstrated that in Bgh challenge the activity of phenylalanine ammonia-lyase is elevated in metchnikowin transgenic plants.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
See 4 more Smart Citations
“…2 Assessment of metchnikowin effects on powdery mildew fungus during its interaction with transgenic barley provided evidence that the antifungal peptide improves the resistance of plant as if it impedes the development of functional haustorium due to increased rate of hypersensitive response (HR) and development of cell wall apposition (CWA). 2 Comprehensive study on possible latent influence of metchnikowin on the defense system of plant revealed that the SAR and ISR pathways as well as redox status of metchnikowin-expressing barley plants are potentiated during interaction with powdery mildew fungus. 99 In Phenylpropanoid pathway, the PAL-1 gene expression profile demonstrated that in Bgh challenge the activity of phenylalanine ammonia-lyase is elevated in metchnikowin transgenic plants.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…2 Despite the fact that the definite cause for specificity has not been elucidated yet, these observations do prospect a promising approach: utilizing AMPs to diminish the devastating consequences of diseases and pests without affecting the plant's essential mutualistic interactions with beneficial symbionts. Clearly, these symbionts are of vital importance for plants in terms of presenting a better fitness via supporting water and mineral uptake as well as strengthening disease resistance.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%
See 3 more Smart Citations